Factors Affecting the Efficient Activity of the Food Market in Fergana Region - Sotvoldiev Nodirbek Jurabaevich (European Science Publishing, 2023)
The article analyzes the political, natural and socio-economic factors affecting the food market of the regions of the Fergana Valley. Based on the analysis of political factors, problems related to the use of transboundary water resources and transport corridors are revealed. Natural factors were evaluated from the point of view of economic conditions. The directions related to socio-economic factors are scientifically based.
Keywords: region, food market, political, natural, socio-economic factors.